2021
DOI: 10.3390/ijerph18041716
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Metabolic Syndrome among the Homeless in Taipei City: A Cross-Sectional Study

Abstract: The safety and health of homeless people are important social issues. Metabolic syndrome (MetS) is a sub-health-risk phenomenon that has been severely aggravated worldwide in recent years. The purpose of this study was to investigate the prevalence and risk factors of MetS among the homeless in Taipei City, Taiwan. In this study, a convenience sampling was conducted at homeless counseling agencies in Taipei City from April 2018 to September 2018. A total of 297 homeless participants were recruited, from whom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Originated from Traditional Chinese Medicine, suboptimal health status (SHS) is de ned as an inter-mediate status with low-quality of health in physiology, psychology and social adaptation between disease and health (2). SHS is also called "sub-health state", "third state" or "grey state" (3), which is similar to chronic fatigue syndrome (4)(5)(6)(7). Remaining in a SHS state may develop into a sub-clinical state and then into a disease state.…”
Section: Introductionmentioning
confidence: 99%
“…Originated from Traditional Chinese Medicine, suboptimal health status (SHS) is de ned as an inter-mediate status with low-quality of health in physiology, psychology and social adaptation between disease and health (2). SHS is also called "sub-health state", "third state" or "grey state" (3), which is similar to chronic fatigue syndrome (4)(5)(6)(7). Remaining in a SHS state may develop into a sub-clinical state and then into a disease state.…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness is widely considered as an individual [1][2][3], social [3][4][5][6], economic [7,8], and political [9] problem that affects the functioning of both individuals and whole of societies. Gu et al [10] report that more than 150 million people worldwide are homeless. A nationwide survey carried out in 2019 at the initiative of the Ministry of Family, Labor and Social Policy showed that there were 30,330 homeless people in Poland, of which 82.1% were men, 14.6% women and 3.3% children [11].…”
Section: Introductionmentioning
confidence: 99%